2011
DOI: 10.1371/journal.pone.0024587
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of Non-Native Forest Insects in the Continental United States

Abstract: Reliable estimates of the impacts and costs of biological invasions are critical to developing credible management, trade and regulatory policies. Worldwide, forests and urban trees provide important ecosystem services as well as economic and social benefits, but are threatened by non-native insects. More than 450 non-native forest insects are established in the United States but estimates of broad-scale economic impacts associated with these species are largely unavailable. We developed a novel modeling appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
441
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(451 citation statements)
references
References 32 publications
5
441
0
5
Order By: Relevance
“…lower timber value, reduced aesthetic value) and social value (e.g. changes to landscape) (Brasier 2008;Boyd et al 2013;Holmes et al 2009;Aukema et al 2011;Liebhold et al 2012;McFarlane et al 2012). However, Smith et al (2007) warn that there is not necessarily a direct relationship between growth in trade and increase in pests, noting that a few commodities may be responsible for many pest introductions.…”
Section: Introductionmentioning
confidence: 99%
“…lower timber value, reduced aesthetic value) and social value (e.g. changes to landscape) (Brasier 2008;Boyd et al 2013;Holmes et al 2009;Aukema et al 2011;Liebhold et al 2012;McFarlane et al 2012). However, Smith et al (2007) warn that there is not necessarily a direct relationship between growth in trade and increase in pests, noting that a few commodities may be responsible for many pest introductions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ash trees were widely planted as landscape trees in urban forests, and an estimate for the undiscounted value of these trees in the United States ranged from $20-60 billion soon after EAB's discovery [11]. A cost projection of EAB in just 25 northeastern communities of the United States for only one decade (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) to treat, remove, and replace landscape ash was $25 billion [49], making EAB the most destructive and costly wood-boring insect to invade the United States [50].…”
Section: Introductionmentioning
confidence: 99%
“…Like other invasive species, EAB has multiple types of impacts: social, economic, and ecological. A 2011 economic analysis concluded that the financial impact of EAB was borne by homeowners and local governments via local expenditures and losses to property value (Aukema et al 2011). The EAB causes 100% mortality of all ash within 10-20 years of introduction (Smitley et al 2008).…”
Section: Introductionmentioning
confidence: 99%